Respuesta :
Answer:
see attached for diagram
a) √13
b) √29
c) 4
Step-by-step explanation:
Equation of the circle: [tex](x + 1)^2 + (y - 3)^2 = 16[/tex]
⇒ center = (-1, 3)
⇒ radius = √16 = 4
Distance between 2 points formula:
[tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
a) let (-1, 3) = [tex](x_1,y_1)[/tex]
let (2, 1) = [tex](x_2, y_2)[/tex]
[tex]\implies \sqrt{(2+1)^2+(1-3)^2} =\sqrt{13}[/tex]
b) let (-1, 3) = [tex](x_1,y_1)[/tex]
let (4, 1) = [tex](x_2, y_2)[/tex]
[tex]\implies \sqrt{(4+1)^2+(1-3)^2} =\sqrt{29}[/tex]
c) let (-1, 3) = [tex](x_1,y_1)[/tex]
let (3, 3) = [tex](x_2, y_2)[/tex]
[tex]\implies \sqrt{(3+1)^2+(3-3)^2} =4[/tex]
![Ver imagen semsee45](https://us-static.z-dn.net/files/d20/c932a22530db207d3ea5716d97777702.png)
Compare with (x-h)^2+(y-k)^2=r^2
- Centre=(h,k)=(-1,3)
- r=4
Distance to (2,1)
- √(2+1)^2+(1-3)^2=√13
Distance to (4,1)
- √(4+1)^2+(1-3)^2=√29
Distance to (3,3)
- √(3+1)^2+(3-3)^2=4
![Ver imagen Аноним](https://us-static.z-dn.net/files/dbc/47dbe6f020e4fcf6c88333aa90e91981.jpg)